The effect of creativity and product innovation on business success (case study at Ruang Kopi Koju Branch Cemara Asri Medan) - Dedy Lazuardi; Ihdina Gustina (International Journal of Applied Finance and Business Studies, 2025)
This study aims to examine the effect of creativity and product innovation on business success, with a case study at Ruang Kopi Koju, Cemara Asri branch in Medan. The research used a quantitative approach with data collected from 99 respondents selected through purposive sampling. Respondents were consumers who had visited the café at least twice. The data were gathered through observation, interviews, and documentation, and analyzed using multiple linear regression. The findings show that both creativity and product innovation have a positive and significant partial effect on business success. Simultaneously, creativity and product innovation also significantly influence business success. The coefficient of determination (R²) test results indicate that both variables jointly contribute to business success at Ruang Kopi Koju. This research highlights the importance of developing creative strategies and innovative products to enhance performance and sustainability in the competitive culinary business sector.